Reduction in the diagnostic interval after the introduction of cancer patient pathways for colorectal cancer in northern Sweden - P. Fjällström; C. Hörnsten; M. Lilja; C. Hultstrand; A. B. Coe; S. Hajdarevic (Scandinavian Journal of Primary Health Care, 2023)
AbstractObjective To compare the diagnostic interval for patients with colorectal cancer before and after the introduction of cancer patient pathways in northern Sweden.Design A retrospective study comparing two cohorts (2012 and 2018) of patients diagnosed with colorectal cancer before and after the introduction of cancer patient pathways in 2016.Setting Three counties in northern Sweden with large sparsely populated areas and some cities (637143 residents ∼5.1 residents/km2).Subjects Patients were included from the Swedish Cancer Register. Electronic health records reviews were performed and linked to socioeconomic data from Statistics Sweden.Main outcome measures Differences in the diagnostic intervals, the patient intervals and the characteristics associated with the longest diagnostic intervals and investigations starting at the emergency department.Results The two cohorts included 411 patients in 2012 and 445 patients in 2018. The median diagnostic interval was reduced from 47 days (IQI 18–99) to 29 days (IQI 9–74) (p < 0.001) after the introduction of cancer patient pathways in general. Though for the cases of cancer in the right-side (ascended) colon, the reduction of the diagnostic interval was not observed and it remained associated with investigations starting at the emergency department.Conclusion Our results indicate that cancer patient pathways contributed to an improvement in the diagnostic interval for patients with colorectal cancer in general, yet not for patients with cancer in the right-side colon.Implication In general, cancer patient pathways seem to reduce the diagnostic interval for colorectal cancer but it is not a sufficient solution for all colorectal cancer localisations.